KINERJA KEUANGAN DAERAH KABUPATEN KOLAKA TIMUR - Maulana, LD Tabdil Akbar (JIM : Journal Of International Management, 2023)
This research is entitled Regional financial performance of East Kolaka Regency. Aims to find out the regional financial performance of East Kolaka Regency. The method is descriptive qualitative approach. The results showed that to realize one of the missions listed in the RPJPN, namely equitable and equitable development by increasing regional development, was carried out by implementing the Regional Autonomy and Fiscal Decentralization policies. The policy is believed to increase the acceleration of development in the region, especially to improve the quality of public services and community welfare. Regional development, including island regions, is part of national development that has strategic importance and value. Transfers to Regions and Village Funds (TKDD) are funds obtained from the APBN which are allocated according to their respective portions to all local governments, both districts / cities and provinces in the context of implementing fiscal decentralization. The implementation of the TKDD budget policy is an instrument of fiscal decentralization policy in order to fund government affairs that fall under regional authority.